Dangerous politics? An analysis of the relationship between political affiliation and assaults on police officers in American counties - Tuttle, Robert, author; Unnithan, Prabha, advisor; Mao, KuoRay, committee member; Berg, Marni, committee member (Colorado State University. Libraries, 2019)
The "War on Cops", a term that denotes a combination of anti-police rhetoric, thinking and politics, has been suggested as resulting in increased violence toward police officers nationwide (Mac Donald 2016). This allegedly began after a racially charged police shooting in Ferguson, Missouri in 2014. Using data from the 2012 Presidential election and the Federal Bureau of Investigation Law Enforcement Officers Killed and Assaulted (2013) report, this study examines the relationship between rates of assault on police officers and political affiliation as determined by the 2012 Presidential election using a stratified random sample of American counties. Findings indicate no statistically significant relationship exists between how a county voted in the 2012 Presidential election and its assault rate on police officers. However, findings do show that the type of weapons used to assault police officers vary significantly by geographic region, as does the average number, and average rate of assaults on police officers in county agencies in 2012.
Keywords: crime rate; police officers; War on Police; law enforcement; assault; political affiliation